SISTEM KEAMANAN SEPEDA MOTOR BERBASIS FACE RECOGNITION - Athalah Pasha Hafidly; Gema Azfajri; Ocsirendi Ocsirendi; Zanu Saputra (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
The need for transportation facilities at this time is very important, one of which is a motorbike. At this time motorbikes are a necessity for the community considering the high level of congestion in big cities in Indonesia, so motorbikes are one of the right options. However, it also makes the level of production of motorcycles increase and the number of purchases increases as well as increases the number of criminal cases of motorcycle theft. Based on this, this research was made to reduce criminal cases of motorcycle theft by implementing a face recognition-based motorcycle security system that uses the ESP32- CAM component as a camera. The method used in making this final project is to recognize faces using the ESP32-CAM component as a camera and to conduct several experiments on the distance between the face to the camera and different light conditions. Based on the results of tests carried out the distance optimal for doing facial recognition is 25 cm to 45 cm. While the percentage of errors in the functional is 8%. The tool can work properly according to its function. Broadly speaking, this research can be applied to motorcycles as additional security.